Depression Relapse during Long-Term Remission due to Media-Amplified Fear during the COVID-19 Pandemic - Ayani, Nobutaka; Matsuoka, Teruyuki; Yamano, Sumihiro; Narumoto, Jin (Case Reports in Psychiatry, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has reoriented societies across the world and placed a significant burden on caring for mental health among its population. In this study, we reported two cases where patients experiencing severe depression with delusions of having COVID-19 required inpatient treatment after long-term remission owing to the negative impact of media reports related to the pandemic. Despite the aggravation of their anxiety, the patients were unable to distance themselves from negative information in attempts to remain informed through media to prevent their families and themselves from being infected. Self-protection through improved media literacy is imperative for people to protect themselves from the fearmongering of the media and infodemic in the present-day scenario.